Potencial do uso de adjuvantes sobre a seletividade do herbicida fomesafen em pré-emergência - Marcon, Natael (2016)
The weeds are a constant threat to the maintenance of the productivity of crops and the use of herbicides is the most used method to control these weeds. The use of the herbicide fomesafen in pre-emergence aims to provide a residual effect over the weed seed bank. Adjuvants are substances that help or modify the action of pesticides in a mix. In sandy soils the phytotoxicity effect of herbicides becomes more pronounced than in clay soils. The adjuvants’ ability of modifying the effectiveness of weed control and the selectivity of herbicides applied in pre-emergence is still not very well comprehended. Thus, it is hypothesized that the use of adjuvants would reduce the selectivity of fomesafen applied pre-emergence in corn and that this effect is more pronounced in soils of lighter texture and higher doses of adjuvant. The objectives of this study were: (a) determine whether the addition of adjuvant modifies the selectivity of herbicide fomesafen in pre-emergence of corn. (b) determine if the adjuvant effect on the selectivity of fomesafen is influenced by soil type. The design used in the experiment was completely randomized design in trifatorial 4x4x3 scheme, qualitative x quantitative x quantitative type, with 3 repetitions. The factor A was composed by 4 proportions of sandy soil, the factor B by 4 doses of fomesafen and the factor C by 3 doses of commercial adjuvant ionic/anionic Energic. The number of emerged plants per experimental unit was made at 7 DAA (days after application). At 7, 14, 21, and 28 DAA, phytotoxicity assessments were conducted and average height, and dry biomass of the DAA 35 aerial part of plants. In evaluations carried out showed the most pronounced effect of herbicide on the two compositions of substrates containing a higher percentage of sand. The adjuvant negatively affected the herbicide in the compositions of 33% and 0%.